Implementation Of Restorative Justice In Criminal Acts Of Narcotics And Of Illegal Drug Abuse In Indonesia - Hamdan, Hamdan; Afnaini, Afnaini (Fox Justi : Jurnal Ilmu Hukum, 2024)
Restorative justice is an alternative approach to law enforcement that focuses on restoring relationships between perpetrators, victims, and communities through dialogue, reconciliation, and reparation of losses. This study aims to analyze the application of restorative justice in criminal acts of narcotics and illegal drug abuse in Indonesia. The method used in this study is an empirical legal approach with qualitative descriptive analysis. The results of the study indicate that the application of restorative justice in resolving criminal acts, especially drug abuse, is very important because the retributive approach that focuses on punishment does not provide significant benefits and can even create new losses for victims and the state. Restorative justice offers a more constructive and inclusive alternative, with the aim of creating peace and restoring losses through dialogue between perpetrators and victims. In Indonesia, Law Number 35 of 2009 emphasizes the need for rehabilitation for addicts, but these efforts have not been optimal. With the application of restorative justice, perpetrators are given the opportunity to improve themselves through medical and social rehabilitation, which can also reduce overcrowding in correctional institutions. Although there are challenges such as the paradigm of law enforcement which is still retributive and public perception that doubts the effectiveness of rehabilitation, cooperation between institutions is very important to ensure that the legal and rehabilitation processes run well, so as to reduce the risk of perpetrators recidivism.